Work incentives at the bottom of the income distribution and for model families in Lithuania - Jekaterina Navickė; Romas Lazutka (University of Essex, Institute for Social and Economic Research (ISER), 2015)
The aim of this paper is to evaluate the impact of cash social benefits on work incentives at the bottom of the income distribution and among selected model family types in Lithuania. The analysis of the work incentives in Lithuania is carried out for the period of 2005-2013 based on a combination of measures estimated using tax-benefit microsimulation model EUROMOD and official OECD/EC indicators. The analysis revealed high disincentives to work at the bottom of the Lithuanian income distribution, dominated by the effect of cash social benefits compared to taxes or social insurance contributions. A strong trade-off between benefit adequacy and work incentives is built into the design of the Lithuanian cash benefit system, that of social assistance in particular. The challenge for policy design is thus to encourage and promote active labour market participation among low earners without eroding the minimum income protection floor.
Keywords: C15; D31; H31; I38; 330; work incentives; microsimulation; model families; Lithuania